Causes and consequential costs of anthropogenic climate change - Novak, David; Synwoldt, Christian (Archives of Business Research, 2020)
On the one hand, this paper examines the costs directly caused by climate change, also com- paring the possible costs for preventing damage; on the other hand, it compares the effects of the radiation propulsion caused by anthropogenic greenhouse gas emissions on anthropogen- ic heat generation through the use of all types of fuels. In addition to the global warming ef- fect caused by anthropogenic heat radiation, there are also local heat islands that are affect- ed by a much greater rise in temperature. Purpose: A cost comparison of the damage caused by climate change and a quantitative com- parison of the direct heat development through the use of fuels with the radiative forcing through anthropogenic greenhouse gas emissions. Design / methodology / approach: In both cases, the research method is based on the analysis of public databases such as the International Energy Agency (IAE), as well as published lit- erature on global energy supply and the Federal Statistical Office. Results: The expected consequential damage caused by climate change will probably present most states with insoluble financial burdens. The radiation propulsion from anthropogenic greenhouse gas emissions makes an 80 times greater contribution to global warming than the anthropogenic heat generation from all types of fuels. Research / practical implications: Future research should show the consequences for the economy and the acquisition of money on the one hand and on the other hand include the ef- fects of global warming and the heat islands, both of which lead to a loss of habitat. Originality / Value: This paper has both the expected follow-up costs in view as well as the causes and effects of anthropogenic greenhouse gas emissions.